Strain induced abnormal grain growth in thermally oxidized Cu2O sheets. (11th February 2021) - Aggarwal, Garima; Singh, Akhilender Jeet; Mehtani, Hitesh Kumar; Balasubramaniam, K. R.
Abstract: Strain induced abnormal grain growth (SIAGG) has been of great interest in metals and metallic alloys but only limited studies of this interesting phenomenon exist in bulk metal oxides. Here, we demonstrate SIAGG in thermally oxidized Cu2 O by cold-working the Cu-foil prior to oxidation. During the cold-work, dislocation density increases at edges and this inhomogeneity in the microstructure give rise to AGG upon oxidative annealing. These abnormally grown grains are prepared without following strict single crystal growth protocols (long duration, high-temperature synthesis) and their diameter ranges from 2 to 10 mm, which are akin to single-crystalline Cu2 O in various applications.